Closing the (incarceration) gap: assessing the socio-economic and clinical indicators of indigenous males by lifetime incarceration status - Stephane M. Shepherd; Ben Spivak; Linda J. Ashford; Isabel Williams; Justin Trounson; Yin Paradies (BMC, 2020)
Abstract Background Approximately 1 in 5 to 1 in 6 Indigenous Australian males are currently imprisoned or have previously been imprisoned. Recent work has also pointed to a widening socio-economic gap within the Indigenous population. Given the myriad social, wellbeing and environmental risk factors associated with justice-involvement, it is conceivable that incarceration may contribute to the increasing disparities found within the Indigenous population. This study aimed to explore the presence and extent of an 'incarceration gap' within the Indigenous population and to uncover which social factors characterise the disparity. Methods The study utilised data from the 2014-5 National Aboriginal and Torres Strait Islander Social Survey (NATSISS). A number of socio-economic, environmental and clinical factors were compared by life-time incarceration status. Chi-square tests were used to examine the association between incarceration status and each of the comparison variables. Results Disparities were observed within the Indigenous Australian population across a number of important health and socio-economic markers by incarceration status - the most pronounced being for educational obtainment - year 10 completion (Never incarcerated 73%, Ever incarcerated 50%), labour force participation (Never incarcerated 56%, Ever incarcerated 26%) and drug/alcohol problems (Never incarcerated 7%, Ever incarcerated 29%). Never-incarcerated Indigenous males yielded aggregate proportions across numerous variables that approximated or matched general Australian population estimates. Conclusions There appears to be evidence for a substantial 'incarceration gap' within the Indigenous Australian population.